Channel congestion control mechanisms for IEEE 802.11P/1609.4 in vehicular ad-hoc networks - Al-Zaghir, Akram Abdullah (2019)
Vehicular ad-hoc networks (VANETs) are a kind of wireless network which has been developed to provide safety-related and commercial service applications on the road. The IEEE 802.11p/1609.4 is a standard protocol designed to support multi-channel operation in VANETs in order to enable the transmission of safety and service applications in different channels. However, the existing analytical models for IEEE 802.11p/1609.4 in VANETs assume that the wireless channel is error-free. Such assumption is inaccurate, especially when dealing with a decentralized wireless network as in VANETs. Moreover, due to the nature of contention-based channel access scheme and the transmission of multiple applications over the CCH sharing a common radio frequency, the safety applications performance is degraded during CCH congestion in high network density scenarios. Therefore, CCH congestion is the major issue encountered while providing Quality of Service (QoS) over VANETs. The first goal of this research is to design analytical models of IEEE 802.11p/1609.4 in VANETs for safety and service application based on Markov chain in the presence of the error-prone channels. The second goal is to develop efficient and reliable channel congestion control mechanisms for IEEE 802.11p/1609.4 in VANETs. To do so, this thesis proposes an Adaptive Multi-Channel Assignment and Coordination (AMAC) scheme for the IEEE 802.11p/1609.4 in VANETs. AMAC scheme initially calculates the Control Channel Busy Ratio (CCBR). Based on the CCBR value, the AMAC scheme performs three functions. First, AMAC scheme decides which channel access scheme should be used in every synchronization interval (SI). Second, AMAC scheme performs an adaptive Peer-to-Peer Negotiation Phase (PNP) mechanism between service providers and users for SCH resource reservations. Thus, the P2P mechanism will be executed either over CCH or SCHs according to the CCH conditions. Lastly, AMAC scheme estimates appropriate contention window sizes values to be used by the vehicles, this approach is called collision-aware packet transmission mechanism. Employing these mechanisms result in higher QoS for different traffic flows over VANETs. The proposed mechanisms are numerically analyzed and then simulated using MATLAB and Network Simulator 2, respectively. For comparison purpose, two existing schemes are considered. One scheme, called Analytical Study of the IEEE 1609.4 MAC in Vehicular Ad Hoc Networks (AS-MAC), is used to compare with the proposed analytical model. The second scheme, called Efficient and Reliable MAC protocol for VANETs (VER-MAC), is used to compare with the proposed AMAC scheme. The numerical and simulation results demonstrate that the proposed analytical model and AMAC scheme outperform the existing AS-MAC model and VER-MAC scheme in terms of five performance metrics studied. These metrics include collision probability, average delay, and packet delivery ratio of safety packets, as well as WSA packets drop probability and system throughput of service packets. For instance, under various vehicles numbers, the results of the proposed AMAC scheme show improvement by 97.90%, 40.79%, 15.27%, 94.23%, and 105.72% for the fiveperformance metrics compared to the VER-MAC scheme, respectively.